"An Entrainment Paradox: How Hysteretic Saltation and Secondary Transport Augment Atmospheric Uptake of Aeolian Source Materials". Issue 10 (11th May 2021) - Rana, Santosh; Anderson, William; Day, Mackenzie
Abstract: Aerodynamic surface stress imposed by the atmospheric surface layer (ASL) drives aeolian sediment transport processes. When the imposed stress exceeds fluid threshold, splashing sand grains release fine (aerosol) particles. This process stops when the imposed stress falls below an impact threshold. Turbulence in the ASL is composed of elongated streaks of relatively high and low streamwise momentum (high‐momentum and low‐momentum regions, HMR and LMR, respectively), and these streaks are aligned with the prevailing winds. Streamwise‐wall‐normal turbulent stress is the concurrent product of fluctuations in streamwise and vertical velocity. These production mechanisms are categorized into quadrants: sweeps, inner interactions, ejections, and outer interactions, where the first two and last two occur within HMRs and LMRs, respectively. Under typical ASL conditions, the time‐averaged shear velocity is bound between 0.3 and 0.5 m/s, demonstrating the importance of fluctuations in mobilizing sand grains via saltation: time‐averaged shear velocity exceeding threshold does not correspond with typical ASL conditions. Given the aforementioned contributions to streamwise‐wall‐normal turbulent stresses from sweeps and ejections, it is self‐evident that under typical conditions only sweeps possess the momentum required to exceed threshold. But, any dust released is trapped by downwelling from aloft; ejections rarely exceed threshold, but they contain the positive vertical velocity needed to entrain. These attributes represent an entrainment paradox. Complementary field data are used to demonstrate the existence of an entrainment paradox. Large eddy simulation has been used to capture space‐time evolution of an idealized ASL and identify mechanistic flow physics central to entrainment. Key Points: An entrainment paradox exists; dust entrainment mechanisms demonstrated Conditional averaging techniques used to identify how the atmospheric surface layer entrains dust Sweeps and outer interactions initiate saltation. Ejections and outer interactions entrain